Uruguay : 2011 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2011)
This 2011 Article IV Consultation highlights that the growth momentum in Uruguay has continued into 2011 but a slowdown is under way, led by weaker exports and slower public investment. Uruguay's economic and financial vulnerabilities are modest, and the government has reduced debt vulnerabilities significantly and built important financial buffers. Executive Directors have commended authorities' skillful macroeconomic management that has underpinned Uruguay's excellent economic performance, lowered public indebtedness, and strengthened buffers against shocks.